Chapter 8: Bulla djandanginy – Challenges and tensions - Buchanan, J.; Collard, Len; Cumming, Ingrid; Palmer, D.; Scott, Kim; Hartley, John (Cultural Science, 2016)
Some of the difficulties confronting a project like this are the consequence of a history of colonisation and institutional oppression of Aboriginal people in south-west Western Australia (Haebich, 1992; 2000; Haebich and Morrison, 2014). It is a history characterised by land theft (Reconciliation, n.d.); a history in which only a minority of the original, Indigenous population survived the first decades of colonisation (Green, 1984; Swain, 1993; Aboriginal Legal Service, 1995), and a history in which that population was then subject to a period of discriminatory legislation and the denigration of Noongar language and culture which lasted well into the late twentieth century (Haebich, 2000). More recently, Noongar language and knowledge has increasingly been celebrated in mainstream cultural life – festivals, theatre, music, literature, exhibitions and the like, along with numerous examples of general urban and street signage and, of course, Welcomes to Country. It has become a major denomination in the currency of identity and belonging in this part of the world.